Discovery of DNA repair inhibitors by combinatorial library profiling - Moeller, Benjamin J. (2011)
Small molecule inhibitors of DNA repair are emerging as potent and selective anti-cancer therapies, but the sheer magnitude of the protein networks involved in DNA repair processes poses obstacles to discovery of effective candidate drugs. To address this challenge, we used a subtractive combinatorial selection approach to identify a panel of peptide ligands that bind DNA repair complexes. Supporting the concept that these ligands have therapeutic potential, we show that one selected peptide specifically binds and non-competitively inactivates DNA-PKcs, a protein kinase critical in double-strand DNA break repair. In doing so, this ligand sensitizes BRCA-deficient tumor cells to genotoxic therapy. Our findings establish a platform for large-scale parallel screening for ligand-directed DNA repair inhibitors, with immediate applicability to cancer therapy.